IMPROVING WORKING CONDITIONS IN THE TRADE UNION SYSTEM - Karimova Nodira Bahodirjanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
Strengthening labor inspection is critical to ensuring high health and safety standards. In many countries, labor inspectorates are becoming a catalyst for many of the processes taking place in government structures, as well as for social partners when it is necessary to create a sustainable tripartite culture of relations. The consequences of globalization will change the role of labor inspection. Developing an integrated one-plant-one inspector approach to labor inspectorate and health and safety management (OSH) and social dialogue systems would mean more impressive and efficient services, making the best use of available resources and meeting the needs of the future. This article analyzes national legislation regarding labor inspection and compliance with international labor standards.